Ability to understand and correctly follow HIV self‐test kit instructions for use: applying the cognitive interview technique in Malawi and Zambia. (25th March 2019) - Simwinga, Musonda; Kumwenda, Moses K; Dacombe, Russell J; Kayira, Lusungu; Muzumara, Agness; Johnson, Cheryl C; Indravudh, Pitchaya; Sibanda, Euphemia L; Nyirenda, Lot; Hatzold, Karin; Corbett, Elizabeth L; Ayles, Helen; et al.
Abstract: Introduction: The ability to achieve an accurate test result and interpret it correctly is critical to the impact and effectiveness of HIV self‐testing (HIVST). Simple and easy‐to‐use devices, instructions for use (IFU) and other support tools have been shown to be key to good performance in sub‐Saharan Africa and may be highly contextual. The objective of this study was to explore the utility of cognitive interviewing in optimizing the local understanding of manufacturers' IFUs to achieve an accurate HIVST result. Methods: Functionally literate and antiretroviral therapy‐naive participants were purposefully selected between May 2016 and June 2017 to represent intended users of HIV self‐tests from urban and rural areas in Malawi and Zambia. Participants were asked to follow IFUs for HIVST. We then conducted cognitive interviews and observed participants while they attempted to complete the HIVST steps using a structured guide, which mirrored the steps in the IFU. Qualitative data were analysed using a thematic approach. Results: Of a total of 61 participants, many successfully performed most steps in the IFU. Some had difficulties in understanding these and made errors, which could have led to incorrect test results, such as incorrect use of buffer and reading the results prematurely. Participants with lower levels of literacy and inexperience with standard pictorial images were more likely to struggle with IFUs. Difficulties tended to be more pronounced among those in rural settings. Ambiguous terms and translations in the IFU, unfamiliar images and symbols, and unclear order of the steps to be followed were most commonly linked to errors and lower comprehension among participants. Feedback was provided to the manufacturer on the findings, which resulted in further optimization of IFUs. Conclusions: Cognitive interviewing identifies local difficulties in conducting HIVST from manufacturer‐translated IFUs. It is a useful and practical methodology to optimize IFUs and make them more understandable.